Analisa Kedalaman Gerusan di Batang Bangko akibat Banjir Bandang Tahun 2016 - Ihsan, Afif Kumala; Marceli, Fidela Erina; Herdianto, Revalin; Sadtim, Sadtim (Jurnal Ilmiah Rekayasa Sipil, 2024)
B Bangko River is one of tributaries in Batanghari River Basin that is originated from Solok selatan Regency. Bangko River had a flash flood on February 8th, 2016 that resulted in vast destruction of paddy field, residences, bridges, and flood plain. At several points along the river, some changes in river morphology were observed. These changes triggered some concern on safety of buildings and residencies along the riverbanks. Hence, there was a need of a study on changes of river behavior laterally and vertically for structural as well as non-structural measures to control morphological changes of the river. This study aims to find scour depth in current conditions due to various discharge schemes that might occur in Batang Bangko. Scour depth was analyzed using Lacey Channel Regime theory, Blench equation (1969), Blodgett equation (1986), and Pemberton dan Lara equation (1984). Design rainfall was calculated using data from Padang Aro and Muaro Labuh rainfall station from year 2007-2021. Sediment gradation was analyzed at laboratory of Civil Engineering Departement, Politeknik Negeri Padang. The results of scour depth from formulas were compared with actual scour depth of Bangko River. The analysis revealed that with Q25 of 492 m3/s results in scour depth of 1,402 m (Lacey Formula (Novak, ET AL., 2007); 0,588 m of Blench formula, 1,535 m of Lacey formula (R.J. Garde, 2006); 1,361 m of Lacey formula (Direktorat Jendral Sumber Daya Air, 2013). This study concluded that actual scour of 1.1 m is the nearest to Lacey formula (Novak, ET AL., 2007).